Analysis of perfumern market in Ukraine. Problems of competitiveness and prospects of development - Самко, Анатолій Васильович; Британова, Тетяна Сергіївна; Samko, A. V.; Britanova, T. S. (Sheffield. Science and education LTD, 2018)
Introduction. In recent years, the market for perfumery has grown steadily in quantitative terms. However, the problem is that the share of domestic products is decreasing every year. Although Ukraine aspires to global recognition, Ukrainian production through outdated technologies can not compete with global brands. Purpose: research and analysis of the main criteria for the development of the domestic market of perfumery products. Subject of research: the blighty market of perfumery articles.